Pengaruh metode problem based learning terhadap peningkatan hasil belajar pendidikan jasmani olahraga dan kesehatan: meta-analisis - I Made Yoga Parwata (Indonesian Journal of Educational Development, 2021)
Educational research using the problem-based learning method to improve learning outcomes for physical education, sports and health has been widely implemented in the world of education and at every level of education, showing positive results. This study aims to determine the effect of the problem based learning model on improving learning outcomes in sports and health physical education. This study uses a meta-analysis method by tracing articles published in the time span from 2015 to 2020, experimental research research design One Group pre-test and post-test design. To determine the merging model with the heterogeneity test, if the p value> 0.05 or the percentage value of I2 is small, the combination model uses the random effect model and with a fixed effect the p value <0.05 or the percentage value of I2 is large. The sample of the meta-analysis research consisted of three articles. Data were analyzed using statistical software JASP version 12.0. The results of a meta-analysis study of the problem-besed learning method on the improvement of learning outcomes in sports and health physical education. Using the fixed effect model, the results of the combined effect of variance between homogeneous studies were p = 0.773> 0.05 and a significant level of p = 0.001 <0.05. and the combined effect size value is 1.92, the effect category is very high and the value of p = 0.001 <0.05. This proves that the problem-based learning method on the improvement of learning outcomes in physical education, sports and health has a very high and significant effect. Penelitian pendidikan dengan menggunakan metode problem based learning terhadap peningkatan hasil belajar pendidikan jasmani olahraga dan kesehatan sudah banyak dilaksanakan pada dunia pendidikan dan pada setiap jenjang pendidikan, menunjukan hasil yang positif. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran problem based learning terhadap peningkatan hasil belajar pendidikan jasmani olahraga dan kesehatan. Penelitian ini menggunakan metode meta-analisis dengan penelusuran artikel yang dipublikasikan dalam rentang waktu dari tahun 2015 sampai dengan 2020, penelitian eksperimen rancangan penelitian One Group pre-test and post-test design. Untuk menentukan model penggabungan dengan uji heterogenitas, bila nilai p>0,05 atau nilai persentase I2 kecil maka model penggabungan menggunakan random effect model dan dengan fixed effect nilai p<0,05 atau nilai persentase I2 besar. Sampel penelitian meta–analisis sebanyak tiga buah artikel. Data dianalisis dengan menggunakan perangkat lunak statistik JASP versi 0.11. Hasil studi meta- analisis metode problem besed learning terhadap peningkatan hasil belajar pendidikan jasmani olahraga dan kesehatan menggunakan model fixed effect, hasil dari efek gabungan varian antara penelitian homogen nilai p = 0,773>0,05 dan nilai taraf signifikan p= 0,001 <0,05. Dan nilai effect size gabungan sebesar 1,92 katagori efek sangat tinggi dan nilai p = 0,001<0,05. Ini membuktikan bahwa metode problem based learning terhadap peningkatan hasil belajar pendidikan jasmani olahraga dan kesehatan sangat memberi pengaruh yang sangat tinggi dan signifikan.